Effect of Nanofillers on the Polarization and Depolarization Current Characteristics of New LLDPE-NR Compound for High Voltage Application - N. A. M. Jamail; M. A. M. Piah; N. A. Muhamad; Z. Salam; N. F. Kasri; R. A. Zainir; Q. E. Kamarudin (Advances in Materials Science and Engineering)
Polymeric nanocomposites in which the nanosize fillers are evenly distributed in the polymer material attract attention as an insulating material due to their ability to enhance the materials performance properties of electrical and mechanical. For high voltage (HV) insulation application, one of the targets is to obtain new insulators with improved dielectric properties. This paper presents the outcome of an experimental study to determine the conductivity level of the linear low-density polyethylene- (LLDPE-)natural rubber (NR) compound, filled with different amount of SiO2 and TiO2 nanofiller by using the polarization and depolarization current (PDC) measurement technique. linear low-density polyethylene (LLDPE) and natural rubber (NR) with the ratio composition of 80 : 20 are selected as a base polymer. The experiment was conducted to find PDC pattern and conductivity variations of each of the LLDPE-NR/SiO2 and LLDPE-NR/TiO2 samples. The results show that the addition of SiO2 filler exhibited less conductivity compared to TiO2 filler with certain percentage. From the study, it can be concluded that LLDPE-NR/SiO2 is a better insulator compared with LLDPE-NR/TiO2.